The Effect of Different Mulches and Bed Sizes on Growth, Yield and Quality of Turmeric (Curcuma longa L.) Under the Mid-Hill Zone of Himachal Pradesh - Ainapur, Shivanand D; Sharma , Happy Dev; Sharma , Vipin; Pathania, Sahil (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was carried out in the Department of Vegetable Science, Dr. YS Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India during kharif, May, 2020–January, 2021 to examine the effect of different mulches and bed sizes on the growth, yield and quality of turmeric. The trial was laid out in randomized complete block design (factorial) with 9 treatment combinations, including 3 mulches (silver-black mulching film, pine needles and dry grass) with 3-bed sizes (9×1 m2, 6×1 m2 and 3×1 m2), which were triplicated. Turmeric yield proved to be significantly affected by mulching materials with silver-black mulching film producing the highest yield (32.01 t ha-1) whereas pine needles produced the lowest yield (23.85 t ha-1). Rhizome length and breadth, the number of primary and secondary rhizomes, dry recovery, essential oil, oleoresin and curcumin content were some of the yield and quality characteristics that have been improved by the use of silver-black mulching film. Bed size also provided a significant effect on the yield of turmeric with the highest (29.03 t ha-1) in bed size 9×1 m2 whereas lowest in 3×1 m2 (25.75 t ha-1). A combination of silver-black mulching film and 9×1 m2 bed size provided the significantly highest turmeric yield (33.56 t ha-1). This study recommends that farmers in Himachal Pradesh’s mid-hill zone to produce turmeric using silver-black mulching film on beds measuring 9×1 m2 for better growth, yield and improved quality of turmeric.